Henri de Lubac y el Concilio Vaticano II: releyendo sus Carnets du Concile (I) - Madrigal Terrazas, Santiago (Estudios eclesiásticos, 2010)
The diary of the Second Vatican Council of the theologian and cardinal Heri de Lubac, Carnets du Concile, have been recently (2007) published. Its pages cover the years 1960-1965, in other words, both the preparatory phase and the four sessions of the Council. Taking advantage of this circumstance, this article goes through this work, placing it in the work and thought of de Lubac, in order to describe accurately his participation and contribution to the Council.